Skilled active liquidity management: Evidence from shocks to fund flows - Rzeźnik, Aleksandra (Journal of empirical finance, 2025)
I examine the active liquidity management of U.S. equity mutual funds facing unexpected, persistent investor withdrawals by exploiting two independent shocks: the 2003 mutual fund scandal and the 2016 introduction of Morningstar Sustainability Ratings. I document that fund managers increase portfolio liquidity by adjusting both equity and cash holdings when subject to sudden, moderate, and prolonged outflows. Among affected funds, those that more aggressively increase portfolio liquidity significantly outperform their less liquidity-focused peers, suggesting that skilled managers employ active liquidity management to minimize costs imposed by redemption obligations. •I exploit two independent shocks to mutual fund net flows.•Fund managers increase portfolio liquidity when subject to sudden outflows.•Skilled managers employ liquidity management to minimize costs im- posed by outflows.